Transformasi struktur ekonomi dan dinamika sektor unggulan Kota Depok - Mifrahi, Mustika Noor; Hafiez, Muhammad Fawwazine (Jurusan Ilmu Ekonomi, Fakultas Bisnis dan Ekonomika, Universitas Islam Indonesia, 2026)
Purpose – This study is to identify leading sectors and analyze the economic structure of Depok City, West Java Province, for the period 2015-2024.Methods – This study uses GRDP data at constant prices and applies the Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift-Share Analysis (SSA), and overlay analysis methods. The results are then integrated through a combined analysis.Findings – The research results show that Depok City's economy is dominated by the service sector and urban-based activities. The electricity, gas, and water supply sectors are classified as non-basic sectors with the potential to become basic sectors in the future. Conversely, the accommodation and food, property, education, healthcare, and other services sectors remain basic sectors, but show a relative weakening trend.Implication – The combined analysis indicates that Depok City's economic development policy needs to focus on strengthening prospective base sectors, accelerating development sectors, revitalizing weakening base sectors, and increasing the productivity of non-base sectors.Originality – This research contributes to the analysis and identification of leading sectors, specifically the economic structure of Depok City, using the Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift-share Analysis (SSA), and overlay analysis. AbstrakTujuan – Penelitian ini bertujuan untuk mengidentifikasi sektor unggulan dan menganalisis struktur ekonomi Kota Depok, Provinsi Jawa Barat pada periode 2015-2024. Metode – Penelitian ini menggunakan data PDRB atas dasar harga konstan dengan metode Location Quotient (LQ), Dynamic Location Quotient (DLQ), dan Shift-Share Analysis (SSA), kemudian hasil ketiganya diintegrasikan melalui analisis overlay. Temuan – Hasil penelitian menunjukkan bahwa perekonomian Kota Depok didominasi oleh sektor jasa dan kegiatan berbasis perkotaan. Sektor listrik dan gas serta pengadaan air tergolong sebagai sektor non-basis yang berpotensi menjadi sektor basis di masa mendatang. Sebaliknya, sektor akomodasi dan makanan, properti, jasa pendidikan, jasa kesehatan, serta jasa lainnya masih berada dalam status sektor basis, namun menunjukkan kecenderungan pelemahan secara relatif.Implikasi – Hasil analisis gabungan menunjukkan bahwa kebijakan pembangunan ekonomi Kota Depok perlu diarahkan pada penguatan sektor basis prospektif, percepatan sektor pengembangan, revitalisasi sektor basis yang melemah, serta peningkatan produktivitas sektor non-basis. Orisinalitas – Penelitian ini berkontribusi dalam menganalisis dan mengidentifikasi sektor unggulan, khususnya struktur ekonomi Kota Depok, dengan pendekatan Location Quotient (LQ), Dynamic Location Quotient (DLQ), dan Shift-Share Analysis (SSA), serta analisis gabungan ketiganya.